Application of psychobiotics in clinical treatment of mental disorders: Neurodevelopmental disorders, neurodegenerative diseases, depression and anxiety - Jingwei Cui; Wenxin Wang; Yue Tang; Siyuan Feng; Hong Liu; Zikai Hao (Interdisciplinary Medicine)
Abstract Psychobiotics are a distinct category of probiotics known for their beneficial effects on human health, particularly in influencing mental well‐being. Typical psychobiotics include genera such as Lactobacillus, Streptococcus, and Bifidobacterium. The gut microbiota influences bidirectional communication between the brain and the gastrointestinal (GI) system. Neurons in the enteric nervous system directly interact with neurotransmitters, short‐chain fatty acids (SCFAs), gut hormones, and anti‐inflammatory cytokines produced by the gut microbiota, thereby affecting signal transmission in the central nervous system. Unlike traditional probiotics, psychobiotics have the capacity to generate or stimulate the host to produce neurotransmitters, SCFAs, gut hormones, and anti‐inflammatory cytokines. It is precisely this potential that has led to the widespread use of psychobiotics over the past decade to improve and treat mental disorders. This article briefly reviews the clinical applications of psychobiotics in improving and treating conditions such as neurodevelopmental disorders, neurodegenerative diseases, depression and anxiety. It is proposed that the novel therapeutic approach of using Bacillus licheniformis as an adjuvant treatment for patients with depression shows a certain degree of feasibility. Finally, this review suggests that the current evidence regarding the improvement and treatment of mental and neurological disorders with psychobiotics is still limited. Further in‐depth research is needed to clarify their effectiveness and mechanisms of action in the clinical management of various mental disorders.